Maternal exposure to ibuprofen can affect the programming of the hypothalamus of the male offspring - Balin, Paola da Silva [UNESP]; Jorge, Bárbara Campos [UNESP]; Leite, Andressa Rejani Ribeiro [UNESP]; Borges, Cibele Santos [UNESP]; Oba, Eunice [UNESP]; Silva, Erick José Ramo [UNESP]; de Barros, Aline Lima [UNESP]; Horta-Júnior, José de Anchieta Castro [UNESP]; Arena, Arielle Cristina [UNESP] (Elsevier, 2020)
Ibuprofen, a non-steroidal anti-inflammatory drug, inhibits the activity of cyclooxygenase enzyme, leading to reduction in Prostaglandin E2 (PGE2) production. Due to the importance of PGE2 in promoting the brain masculinization in male fetus, this study aimed to evaluate the effects of in utero and lactational exposure to ibuprofen and their late repercussions on reproductive parameters in male rats. Pregnant rats were exposed to ibuprofen (10, 30 or 60 mg/kg) or vehicle (control group) per gavage daily from gestational day 15 to day 21 after birth, and late reproductive effects were assessed during the sexual development and in the reproductive adult life in the male offspring. Males exposed to ibuprofen had a decrease in body weight and anogenital distance, as well as a delay in the ages of testicular descent and preputial separation. In adulthood, there was a decrease in the Leydig cells nuclei volume, testosterone levels and percentage of normal sperm morphology. All animals exposed to ibuprofen presented male copulatory behavior, however, in the presence of another male, they also presented a female-typical behavior. Maternal exposure to ibuprofen during the sensitive windows of brain development adversely impacted the reproductive parameters of male rats, suggesting an incomplete masculinization of the hypothalamus.
Keywords: Brain sexual differentiation; Preoptic area; Prostaglandins; Sexual behavior; Sexually dimorphic nucleus